2010
DOI: 10.1523/jneurosci.4023-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Origin and Molecular Specification of Globus Pallidus Neurons

Abstract: The mechanisms controlling the assembly of brain nuclei are poorly understood. In the forebrain, it is typically assumed that the formation of nuclei follows a similar sequence of events that in the cortex. In this structure, projection neurons are generated sequentially from common progenitor cells and migrate radially to reach their final destination, whereas interneurons are generated remotely and arrive to the cortex through tangential migration. Using the globus pallidus as a model to study the formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
163
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(177 citation statements)
references
References 63 publications
14
163
0
Order By: Relevance
“…3B). Costaining with the GP marker Nkx2-1 (21,23) demonstrated that the vast majority of GP cells express Celsr3 (Fig. 3C to E fied, 318 cells are Celsr3 ϩ ) (Fig.…”
Section: Inhibition Of Celsr3 By Nrsfmentioning
confidence: 93%
See 2 more Smart Citations
“…3B). Costaining with the GP marker Nkx2-1 (21,23) demonstrated that the vast majority of GP cells express Celsr3 (Fig. 3C to E fied, 318 cells are Celsr3 ϩ ) (Fig.…”
Section: Inhibition Of Celsr3 By Nrsfmentioning
confidence: 93%
“…Malfunctions of GP lead to several neuropathological conditions, such as Parkinson's disease, as well as many neuropsychiatric diseases (19). The mouse GP, which corresponds to the GPe in primates, contains approximately 44% of parvalbumin-positive (PV ϩ ) neurons and 1% of calretinin-positive (CR ϩ ) interneurons, but calbindin-positive (CB ϩ ) cells are rare (20,21). The GP is traditionally thought to be derived from the medial ganglionic eminence (MGE) (22); however, recent studies have revealed that, in addition to MGE, subpopulations of GP cells are also generated from the lateral ganglionic eminence (LGE) and preoptic area (POA) (21, 23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, anatomical dichotomy has often been described in the GP [Hoover and Marshall, 2002, Cooper and Stanford, 2002, Nobrega-Pereira et al, 2010. For instance, a group of proenkephalin positive neurons that preferentially target the striatum [Hoover and Marshall, 2002] and a small population of calretinin positive interneurons [Cooper and Stanford, 2002] have been reported.…”
Section: Intrinsic Gpe Structurementioning
confidence: 99%
“…For instance, a group of proenkephalin positive neurons that preferentially target the striatum [Hoover and Marshall, 2002] and a small population of calretinin positive interneurons [Cooper and Stanford, 2002] have been reported. Based on fate mapping analysis, even five neural populations have been identified in the mouse GP which differ in progenitor lineage and partly in their embryonic domains [Nobrega-Pereira et al, 2010]. Recently, Mallet et al [2012] combined anatomical and electrophysiological characteristics of classes of GP neurons.…”
Section: Intrinsic Gpe Structurementioning
confidence: 99%